2017
DOI: 10.3934/jimo.2017019
|View full text |Cite
|
Sign up to set email alerts
|

A numerical scheme for pricing American options with transaction costs under a jump diffusion process

Abstract: In this paper we develop a numerical method for a nonlinear partial integro-differential complementarity problem arising from pricing American options with transaction costs when the underlying assets follow a jump diffusion process. We first approximate the complementarity problem by a nonlinear partial integro-differential equation (PIDE) using a penalty approach. The PIDE is then discretized by a combination of a spatial upwind finite differencing and a fully implicit time stepping scheme. We prove that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Remark 3.2. The upwind finite difference method has been used for solving various types of differential equations (see, for example, [14,28,19,13,16,17]). In particular it is used for a nonlinear Black-Scholes equation arising in pricing a conventional option in [16] in which the authors also prove the convergence of the method by showing that it is consistent, monotone, stable.…”
Section: )mentioning
confidence: 99%
“…Remark 3.2. The upwind finite difference method has been used for solving various types of differential equations (see, for example, [14,28,19,13,16,17]). In particular it is used for a nonlinear Black-Scholes equation arising in pricing a conventional option in [16] in which the authors also prove the convergence of the method by showing that it is consistent, monotone, stable.…”
Section: )mentioning
confidence: 99%
“…scheme is normally used to approximate (1)-(2) by a finite-dimensional obstacle or constrained optimization problem (see, for example, [11,12,21,42]). Numerical solution of the resulting large-scale discretied and finite-dimensional optimization problems has been discussed in the open literature such as [11,12,25,26,42,27,23]. While these existing methods provide some effective and efficient tools for solving obstacle problems without uncertainties, how to find a solution to a large-scale finite-dimensional obstacle problem effectively in the presence of parameter uncertainties still remains a challenge.…”
Section: Song Wangmentioning
confidence: 99%
“…As mentioned before, A(p) in 3is usually a positive-definite symmetric matrix if an appropriate numerical scheme such as one of those in [22,42,27,23] is used for the discretization of (1). Thus, there exists a positive constant α such that…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors in [8] proposed a mathematical model in finance to calculate the option price of a European contract. After that, empirical evidences indicated that their model assumptions on the log-normality of the return of the underlying asset and constant volatility are usually inconsistent with market prices, for more refer to the discussions in [26].…”
mentioning
confidence: 99%